Portrait of Project-Based Management Control System in Property Companies - Nihad Ba’syir; Adhitya Bayu Suryantara (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research was conducted to explore how property companies in the city of Mataram implement management control systems in their companies to complete a housing development project until completion and generate profits in the form of earnings. A qualitative approach using a case study method was employed in this research. The object of this research is PT. X, one of the property companies that is quite established and well-known among the community in the city of MataramThe data collection methods used in this research include observations, in-depth and structured interviews, as well as documentation. After the data were successfully collected, data analysis would then be conducted to confirm the data so that it could be presented. After presenting the data, conclusions and recommendations were drawn. The results of this research indicate that the project-based management control system at PT X is effective and efficient in the detailed strategic planning conducted to ensure that everything runs smoothly and achieves the desired and established goals Effective and efficient budgeting is established by creating highly detailed budgets, from land purchases to the completion of housing construction projects